VRPTW Distribution Route Determination with Rigid and Flexible Time Window and Assignment Based on Number of Demand - Keynobi, Fikri; Wirdianto, Eri; Zidanne, Muhammad (TALENTA Publisher, 2025)
Vehicle routing problems (VRP) are common in many companies and play an important role in distribution and logistics. Effective routing can significantly reduce expenses and increase customer satisfaction. The research entitled